Implementation of Government Policies to Handling The Covid-19 Pandemic in Indonesia - Tivalen Dwirara Anggraini (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
The spread and addition of COVID-19 cases are certainly dangerous. Government policies and commitments from the community play an important role in the process of accelerating the handling of COVID-19. This study aims to review the policies that have been issued by the government to deal with the COVID-19 pandemic and the public to these policies. The method used in this study is a literature review. The results of this study indicate that various policies have been issued by the government in handling COVID-19 such as policies for implementing health protocols, Large-Scale Social Restrictions, and policies for fulfilling COVID-19 vaccinations in the community. The research concludes that the government and the role of the community are very important that their existence greatly influences the implementation of these policies. Public awareness is the key to success in breaking the transmission of the coronavirus, the government needs to make firm policies in efforts to handle COVID-19, and education to the public must be carried out massively.